2018
DOI: 10.1111/mpp.12752
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses underlying nonhost resistance of Citrus limon against Xanthomonas campestris pv. campestris

Abstract: Summary Citrus is an economically important fruit crop that is severely afflicted by citrus canker, a disease caused by Xanthomonas citri ssp. citri (X. citri); thus, new sustainable strategies to manage this disease are needed. Although all Citrus spp. are susceptible to this pathogen, they are resistant to other Xanthomonas species, exhibiting non‐host resistance (NHR), for example, to the brassica pathogen X. campestris pv. campestris (Xcc) and a gene‐for‐gene host defence response (HDR) to the canker‐causi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…These results indicated that PeaFJ1 and HA4-1 had different virulence profiles, and PeaFJ1 was more virulent to most peanut varieties than HA4-1. The hypovirulence of HA4-1 to certain peanut varieties is probably owed to host specificity at genotype levels, which is closely related to the type III effectors, since T3Es always narrow the host range when certain effectors are specifically recognized as avirulence factors by the host ( Jones and Dangl, 2006 ; Chiesa et al, 2019 ; Cho et al, 2019 ; Tan et al, 2019 ). These data suggest that HA4-1 may contain an avirulence T3E(s) that induces bacterial wilt disease resistance in A184.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that PeaFJ1 and HA4-1 had different virulence profiles, and PeaFJ1 was more virulent to most peanut varieties than HA4-1. The hypovirulence of HA4-1 to certain peanut varieties is probably owed to host specificity at genotype levels, which is closely related to the type III effectors, since T3Es always narrow the host range when certain effectors are specifically recognized as avirulence factors by the host ( Jones and Dangl, 2006 ; Chiesa et al, 2019 ; Cho et al, 2019 ; Tan et al, 2019 ). These data suggest that HA4-1 may contain an avirulence T3E(s) that induces bacterial wilt disease resistance in A184.…”
Section: Resultsmentioning
confidence: 99%
“…() and conductivity was measured according to Chiesa et al . (). For Agrobacterium ‐mediated transient expression, strains preparation and induction were conducted as described by Enrique et al .…”
Section: Methodsmentioning
confidence: 97%
“…Referring to the method of Chiesa [ 27 ] with slight modifications, firstly, the bacteria cultured to the logarithmic phase were treated with different concentrations (1/2 MIC and MIC) of CEO at 37 °C for 4 h, and a control group was set. After centrifuging at 5000× g for 5 min, we collected the precipitate, washed it three times with PBS and resuspended it.…”
Section: Methodsmentioning
confidence: 99%